Applying Nativist Theory in Arabic Language Acquisition: Insights from the “Ismu Fil Arabia” Activity in Elementary Schools - Syuhadak; M. Abdul Hamid; Mohammad Samsul Ulum; Mamluatul Hasanah; R. Taufiqurrochman (Journal of Advanced Research in Social Sciences and Humanities, 2023)
Aim: The study aims to explore Nativist theory application in Indonesian school environment. Nativism has been a pessimistic topic when discussing its implementation in the context of children’s education. This happens because the flow of its universal ability, which has been carried since birth, is not influenced by external elements like an Arabic language environment gifted by a teacher’s values. In fact, the understanding of Nativism is not that shallow; there are several indicators that are missed when looking at implicit phenomena in the role of Arabic language acquisition without involving this understanding.Methodology: Using a phenomenological approach related to the "ISMU fil Arabia" activity, the researcher would explain the Nativism learning method in the Muhammadiyah Primary / Elementary school environment in Surabaya, Indonesia. The target informants in this study are people who are directly involved in the implementation of activities such as home classroom teachers, teachers of Islam, Muhammadiyah, and Arabic language. (ISMUBA) and teachers who are members of the Student Work Unit from relevant schools.Findings: It has been proven to have produced students who are able to speak Arabic without external limitations from the school environment and teachers, which has become one of the sources of school promotion to gain its accreditation value that can be achieved for free.Implications/Novel Contribution: The research affirms that a hybrid approach—merging linguistic theory with educational and sociological insights—provides a more comprehensive understanding of Arabic language acquisition in elementary Islamic education settings. This synthesis not only enriches the pedagogical practice in programs such as ISMU fil Arabia, but also contributes to the broader discourse on the intersection between language acquisition, educational identity, and cultural formation in Islamic schooling.